“Almost Soviet Father”: An Experience of Microhistorical Research of Rural Confessional History in 1940s—1970s - A. V. Apanasenok (Научный диалог, 2022)
The problem of the possibility of a fruitful study of the rural parish history of the Soviet period through microhistorical analysis is raised. For discussion, the experience of researching the fate of a small Old Believer community is proposed. Both archival documents and interview materials are used. The purpose of the publication is to show some factors of the reproduction of traditional religious culture on the Soviet collective farm of the 1940s—1970s and at the same time demonstrate the heuristic potential of combined archival and field work. The author focuses on the figure of a priest who managed to restore and strengthen his parish, despite the previous dispossession and destruction of the prayer house. The cohesion of the community, outstanding personal qualities, as well as the ability of believers to practically harmonize Christian and Soviet values became the conditions for his success is shown in the article. The adoption of Soviet cultural norms, excluding atheism, is considered in the work as the most important factor in the survival of the Old Believer community. The expediency of verifying the data of official Soviet documentation by referring to oral history is demonstrated in the study. It is pointed out that in the materials of the USSR civil servants devoted to confessional phenomena, strict facts could be combined with false interpretations.